Solar Spectral and Module Temperature Influence on the Outdoor Performance of Thin Film PV Modules Deployed on a Sunny Inland Site - G. Nofuentes; J. de la Casa; M. Torres-Ramírez; M. Alonso-Abella (International Journal of Photoenergy)
This work aims at analysing the influence of both module temperature and solar spectrum distribution on the outdoor performance of the following thin film technologies: hydrogenated amorphous silicon (a-Si:H), cadmium telluride (CdTe), copper indium gallium selenide sulfide (CIGS), and hydrogenated amorphous silicon/hydrogenated microcrystalline silicon hetero-junction (a-Si:H/μc-Si:H). A 12-month experimental campaign carried out in a sunny inland site in which a module of each one of these technologies was tested and measured outdoors has provided the necessary empirical data. Results show that module temperature exerts a limited influence on the performance of the tested a-Si:H, CdTe, and a-Si:H/μc-Si:H modules. In contrast, the outdoor behaviour of the CIGS module is the most affected by its temperature. Blue-rich spectra enhance the outdoor behaviour of the a-Si:H and a-Si:H/μc-Si:H modules while it is the other way round for the CIGS module. However, the CdTe specimen shows little sensitivity to the solar spectrum distribution. Anyway, spectral effects are scarcely relevant on an annual basis, ranging from gains for the CIGS module (1.5%) to losses for the a-Si:H module (1.0%). However, the seasonal impact of the spectrum shape is more noticeable in these two materials; indeed, spectral issues may cause performance gains or losses of up to some 4% when winter and summer periods are considered.